La concordanza negativa nel volgare veneto delle Origini (Atti del Sodalizio Glottologico Milanese, 2019)
In this paper I analyse the variation displayed by Old Venetan texts regarding Negative Concord with preverbal items. Venetian displays strict Negative Concord, while Paduan and Veronese have mandatory preverbal negation only with negative adverbs and the negative coordination particle. With argumental quantifiers (like ‘nobody’) preverbal negation is very rare in these varieties. I propose that the distribution is driven by two factors: the category of the preverbal negative item, and its structural position above the inflected verb. KEYWORDS: Old Venetan, Italian dialects, syntax, negation, negative concord